Developing Learning Material for Animation 2D Instruction in Vocational High Schools - Septian Rheno Widianto; Rahmatiah; B. Syukroni Baso; Nana Citrawati Lestari; Arifin (Institute of Computer Science (IOCS), 2022)
Changes in information and communication technology necessitate rapid adaptation in the application of technology to the learning process in education. As participants in learning activities, teachers are required to be able to develop engaging, technology-based learning models, one of which is the use of interactive multimedia learning resources. In vocational high school learning, there are 2D animation courses that teach the fundamentals of creating 2D animation. This subject is interesting because it can be a forum for students' creative skills; therefore, it is highly appropriate to use Interactive Learning media, which can reduce a static atmosphere and create an effective, interesting, interactive, and enjoyable learning process. In this study, interactive multimedia learning is implemented in 2D animation classes in vocational high schools by modifying the 2D animation learning curriculum. The approach of application development employs the Multimedia Development Life Cycle model, which comprises of the steps of concept, design, material collecting, assembly, and testing. The concept of multimedia design employs the notion of simplicity, which tries to make the material's content not overly complex, concise, clear, instructive, and convincing in order to pique students' interest. Testing the program utilizing a blackbox technique that demonstrates the application has functioned properly and is in compliance with the user needs analysis.